Penyuluhan Pemanfaatan Jahe Merah Sebagai Tanaman Berkhasiat Antiradang di Desa Maku Kecamatan Dolo, Kabupaten Sigi, Sulawesi Tengah - Ficanata Adhiguna Toding; Ni Made Dewi Sinta; Febrianti F (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Spices are a group of plants that are often used as traditional medicine. Most of the spice plants have properties for the health of the body, including being able to provide a strong deterrent (preventive) against various diseases and can improve the health condition of the body (promotive). The purpose of carrying out Community Service Activities is to increase understanding of the benefits of plants that are around, especially red ginger where the benefits of red ginger are very helpful in reducing joint pain, especially for elderly people who are in Maku Village, Dolo sub-district, Sigi district, Central Sulawesi. maku is a place where spices are produced, especially red ginger rhizome (Zingiber officinale var. Rubrum) and the benefits of red ginger which are very efficacious and have been proven in several studies to be used as anti-inflammatories. The research method is to carry out counseling by distributing leaflets to the community, making Toga gardens, health checks and distributing groceries. The speaker distributed questionnaires to the community. Based on the percentage value of the indicators in the questionnaire that had been distributed, the average percentage of community/partner satisfaction with PkM activities in Maku Village, Dolo District, Sigi Regency was 90%.